Preparation method and application of TiO2 nano array composite electrode
By growing Fe-doped BiOBr sheets on TiO2 nanoarray composite electrodes, it forms an angle with TiO2 nanotubes, the problem of loading materials blocking the pipe port is solved, the light absorption capacity and catalytic activity are improved, and new pollution is achieved efficient degradation of substances.
Patent Information
- Application Number
- CN202411677801.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The existing TiO2 nanoarray composite electrode has the problem of loading materials blocking the pipe port, resulting in a decrease in light absorption capacity and a weakened catalytic activity, affecting the ability to control new pollutants.
By growing Fe-doped BiOBr sheets on TiO2 nanotubes, an angle between them and TiO2 nanotubes is formed, so as to avoid the loading material from blocking the tube ports and improve light absorption capacity and catalytic activity.
Effectively improve the light absorption capacity and catalytic activity of the composite electrode, and improve the degradation capacity of new pollutants, especially in the degradation of 17α-ethynylestradiol and chloramphenicol, achieving high efficiency of 99.2% and 97.6%. Degradation rate.
Smart Images

Figure CN119461591A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoelectric catalytic composite materials and relates to a preparation method of a TiO2 nano-array composite electrode and application thereof. Background Art
[0002] With the rapid development of industrialization and modernization, new pollutants have emerged. New pollutants refer to a class of chemical substances that can be detected in the environment and natural ecosystems, which can pose greater risks and hidden dangers to human health and environmental safety even if they enter in low doses. They mainly include persistent organic pollutants, endocrine disruptors, antibiotics, microplastics, etc. that are controlled by international conventions. Their spread and accumulation in the environment pose a serious threat to the entire ecosystem and human health.
[0003] In the water environment, most new pollutants exist in the form of mixed pollutants, which may produce synergistic or antagonistic effects, making them more difficult to treat. Photoelectric coupled catalytic technology, as a new advanced oxidation technology that combines photocatalysis with electrocatalysis, can effectively overcome the disadvantage of easy recombination of photogenerated electron-hole pairs in the photocatalytic process, and give full play to the advantages of electrocatalysis. At the same time, it also has the advantages of no secondary pollution, cheap and easy to obtain materials, etc., and has broad application prospects in the treatment of new pollutants.
[0004] TiO2 nanotubes are widely used in photoelectric coupled catalytic technology due to their large specific surface area, full contact with electrolyte, and good chemical stability. They are mainly in the form of TiO2 nano-array composite electrodes. However, the current TiO2 nano-array composite electrodes have the problem of the loading material blocking the tube mouth, which leads to the decrease of the light absorption capacity of the composite electrode, and finally the catalytic activity of the composite electrode is weakened, affecting the ability of the composite electrode to treat new pollutants.
[0005] Therefore, it is necessary to provide a preparation method and application of a TiO2 nanoarray composite electrode to avoid clogging of the tube orifice by the loaded material, improve the catalytic activity of the composite electrode, and enable the TiO2 nanoarray composite electrode to have better new pollutant degradation capabilities. Summary of the invention
[0006] In order to overcome the problems in the background technology, the TiO2 nanoarray composite electrode prepared by the preparation method of the present invention forms an angle between the Fe-doped BiOBr (Fe / BiOBr) sheet grown on the TiO2 nanotube and the TiO2 nanotube, which effectively avoids the situation where the load material blocks the tube mouth, thereby improving the light absorption capacity of the composite electrode, thereby improving the catalytic activity of the TiO2 nanoarray composite electrode, and ultimately improving the catalytic degradation ability of the composite electrode to pollutants.
[0007] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0008] In one aspect, the present invention provides a method for preparing a composite electrode in which Fe-doped BiOBr is vertically grown on a TiO2 nanoarray. The preparation method comprises the following steps:
[0009] (1) ultrasonically cleaning the titanium foil and then polishing it;
[0010] (2) using the titanium foil treated in step (1) as an anode and the titanium plate as a cathode to perform electrolytic oxidation, washing the oxidized titanium foil, and then annealing to obtain anatase TiO2 nanotubes;
[0011] (3) dissolving bismuth nitrate pentahydrate and potassium bromide in ethylene glycol and stirring, and then adding ferric nitrate nonahydrate to obtain a Fe / BiOBr precursor solution;
[0012] (4) hydrothermally reacting the Fe / BiOBr precursor solution obtained in step (3) with the anatase TiO2 nanotubes obtained in step (2), and then washing and drying the reaction product to obtain a TiO2 nanoarray composite electrode.
[0013] Preferably, in step (1), the titanium foil is ultrasonically cleaned using acetone, anhydrous ethanol and ultrapure water in sequence, with each washing lasting 15 to 30 minutes.
[0014] Preferably, in step (1), the polishing liquid used for polishing is prepared from hydrofluoric acid, nitric acid and water in a volume ratio of HF:HNO3:H2O=1:4:5, and the polishing time is 30 to 60 seconds.
[0015] Preferably, in step (2), the electrolyte used for electrolytic oxidation is prepared from water, ethylene glycol and ammonium fluoride. First, water and ethylene glycol are mixed in a volume ratio of H2O:C2H6O2=1:49 to obtain a solvent, and then ammonium fluoride is added to the solvent in a mass ratio of NH4F:solvent=1:399 to obtain an electrolyte.
[0016] Preferably, in step (2), the electrolytic oxidation voltage is 30 V and the electrolytic oxidation time is 1 to 3 hours.
[0017] Preferably, in step (2), the annealing temperature is 450-550° C., the heating rate is 3-7° C. / min, and the holding time is 1-3 h.
[0018] Preferably, in step (3), the amounts of bismuth nitrate pentahydrate and potassium bromide are equal, the solid-liquid ratios of bismuth nitrate pentahydrate and potassium bromide to ethylene glycol are both 1-3 mmol:500 ml, and the solid-liquid ratio of ferric nitrate nonahydrate to ethylene glycol is 5-7 mmol:5000 ml.
[0019] Preferably, in the step (3), after adding ferric nitrate nonahydrate, stirring is continued for 1 to 3 hours to obtain a Fe / BiOBr precursor solution.
[0020] Preferably, in step (4), the hydrothermal reaction temperature is 100-200° C., and the reaction time is 9-11 h.
[0021] Another aspect of the present invention provides the use of the TiO2 nano-array composite electrode in the degradation of 17α-ethynyl estradiol and chloramphenicol.
[0022] Beneficial effects of the present invention:
[0023] 1. The TiO2 nanoarray composite electrode prepared by the present invention can effectively prevent the Fe / BiOBr sheet from clogging the nanotube orifice, improve the light absorption capacity of the composite electrode, and allow the composite electrode to exhibit strong light absorption capacity in the entire visible light band, with high stability and excellent visible light response, so that the composite electrode has a better ability to degrade pollutants.
[0024] 2. The TiO2 nano-array composite electrode prepared by the present invention greatly increases the wetting and exposed specific surface area of the Fe / BiOBr sheet, thereby improving the catalytic activity of the TiO2 nano-array composite electrode, thereby improving the catalytic degradation ability of the composite electrode to pollutants
[0025] 3. In the process of degrading new pollutants, the present invention does not produce secondary pollutants such as toxic heavy metals.
[0026] 4. The composite electrode of the present invention has a highly efficient degradation effect on 17α-ethynyl estradiol (EE2) and chloramphenicol (CAP) in water, with degradation rates of 99.2% and 97.6%, respectively. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 These are EDS images of the composite electrodes prepared in Comparative Example 1, Comparative Example 2, and Example 1, wherein (a) is the composite electrode prepared in Comparative Example 2, (b) is the composite electrode prepared in Comparative Example 1, (c) is the composite electrode prepared in Example 1, and (d1-d6) are the elemental compositions of the composite electrodes in Example 1.
[0028] Figure 2 The XRD diagrams of the composite electrodes prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown.
[0029] Figure 3 The cyclic voltammetry (CV) curves of the composite electrodes prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown.
[0030] Figure 4 The UV-visible diffuse reflectance spectra of the composite electrodes prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown.
[0031] Figure 5 This is a comparison chart of the degradation effects of the composite electrodes prepared in Example 1, Comparative Example 1, and Comparative Example 2 in a mixed system. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with specific embodiments.
[0033] In the embodiments and comparative examples of the present invention, chemical reagents not specifically described are
[0034] Example 1
[0035] This embodiment prepares the TiO2 nanoarray composite electrode according to the following steps:
[0036] (1) High-purity titanium foil (Ti≥99.99%, thickness 0.3 mm) was cut into a 3.0*4.0 cm rectangle, and the cut titanium foil was ultrasonically washed in acetone, anhydrous ethanol and ultrapure water for 15 min respectively.
[0037] (2) The titanium foil was then immersed in a polishing solution with a volume ratio of HF:HNO3:H2O=1:4:5 for chemical polishing for 35 seconds.
[0038] (3) The polished titanium foil is used as the anode and the titanium plate is used as the cathode, and the electrolyte is placed in the electrolyte for oxidation for 2 hours at an oxidation voltage of 30 V. The electrolyte is prepared from water, ethylene glycol, and ammonium fluoride. First, water and ethylene glycol are mixed at a volume ratio of H2O:C2H6O2=1:49 to obtain a solvent, and then ammonium fluoride is added to the solvent at a mass ratio of NH4F:solvent=1:399 to obtain the electrolyte.
[0039] (4) After the electrolytically oxidized titanium foil is rinsed with ultrapure water, the titanium foil is placed in a muffle furnace for annealing. The muffle furnace is set to heat up to 450°C at a heating rate of 5°C / min and kept at that temperature for 2 hours. After natural cooling, anatase titanium dioxide nanotubes are obtained.
[0040] (5) 0.2 mmol Bi(NO3)3·5H2O and KBr were dissolved in 50 mL C2H6O2, and then 0.06 mmol Fe(NO3)3·9H2O was added to the mixed solution under magnetic stirring for 1 h to obtain a Fe / BiOBr precursor solution;
[0041] (6) The Fe / BiOBr precursor solution was then transferred to a 100 mL polytetrafluoroethylene liner loaded with anatase titanium dioxide nanotubes, and the Fe / BiOBr precursor solution and anatase titanium dioxide nanotube mixture were heated to 160°C and maintained for 10 h. After sufficient cooling, the reaction product was rinsed several times alternately with anhydrous ethanol and ultrapure water, and then placed in a vacuum drying oven and vacuum dried at 60°C for 6 h to obtain a TiO2 nanoarray composite electrode. The nanoarray composite electrode prepared in this example is recorded as F / B-TNTAs.
[0042] The F / B-TNTAs prepared in this example were subjected to transmission electron microscopy scanning, energy dispersive X-ray spectroscopy experiment, X-ray diffraction, cyclic voltammetry scanning, UV-light diffuse reflection, and degradation effect experiments, and the results were as follows: Figure 1-5 shown.
[0043] Example 2
[0044] This embodiment prepares the TiO2 nanoarray composite electrode according to the following steps:
[0045] (1) High-purity titanium foil (Ti≥99.99%, thickness 0.3 mm) was cut into a 3.0*5.0 cm rectangle, and the cut titanium foil was ultrasonically washed in acetone, anhydrous ethanol and ultrapure water for 30 min respectively;
[0046] (2) The titanium foil was then immersed in a polishing solution with a volume ratio of HF:HNO3:H2O=1:4:5 and chemically polished for 60 seconds;
[0047] (3) The polished titanium foil was used as the anode and the titanium plate was used as the cathode, and placed in an electrolyte and oxidized at an oxidation voltage of 30 V for 1 h;
[0048] (4) After the electrolytically oxidized titanium foil is rinsed with ultrapure water, the titanium foil is placed in a muffle furnace for annealing. The muffle furnace is set to heat up to 500° C. at a heating rate of 3° C. / min, and the temperature is kept for 3 h. After the temperature is naturally lowered, anatase titanium dioxide nanotubes are obtained;
[0049] (5) 0.1 mmol Bi(NO3)3·5H2O and KBr were dissolved in 50 mL C2H6O2, and then 0.05 mmol Fe(NO3)3·9H2O was added to the mixed solution under magnetic stirring for 3 h to obtain a Fe / BiOBr precursor solution;
[0050] (6) The Fe / BiOBr precursor solution was then transferred to a 100 mL polytetrafluoroethylene liner loaded with titanium dioxide nanotubes, and the Fe / BiOBr precursor solution and anatase titanium dioxide nanotube mixture were heated to 200°C and maintained for 9 h. After sufficient cooling, the reaction product was alternately rinsed several times with anhydrous ethanol and ultrapure water, and then placed in a vacuum drying oven and vacuum dried at 60°C for 6 h to obtain a nanoarray composite electrode.
[0051] The nanoarray composite electrode prepared in this example has similar performance to that of Example 1.
[0052] Example 3
[0053] This embodiment prepares the TiO2 nanoarray composite electrode according to the following steps:
[0054] (1) High-purity titanium foil (Ti≥99.99%, thickness 0.3 mm) was cut into a 2.0*5.0 cm rectangle, and the cut titanium foil was ultrasonically washed in acetone, anhydrous ethanol and ultrapure water for 20 min respectively;
[0055] (2) The titanium foil was then immersed in a polishing solution with a volume ratio of HF:HNO3:H2O=1:4:5 for chemical polishing for 30 seconds;
[0056] (3) The polished titanium foil was used as the anode and the titanium plate was used as the cathode, and placed in an electrolyte and oxidized for 3 h at an oxidation voltage of 30 V;
[0057] (4) After the electrolytically oxidized titanium foil is rinsed with ultrapure water, the titanium foil is placed in a muffle furnace for annealing. The muffle furnace is set to heat up to 550° C. at a heating rate of 7° C. / min, and the temperature is kept for 1 h. After the temperature is naturally lowered, anatase titanium dioxide nanotubes are obtained;
[0058] (5) 0.3 mmol Bi(NO3)3·5H2O and KBr were dissolved in 50 mL C2H6O2, and then 0.07 mmol Fe(NO3)3·9H2O was added to the mixed solution under magnetic stirring for 2 h to obtain a Fe / BiOBr precursor solution;
[0059] (6) The Fe / BiOBr precursor solution was then transferred to a 100 mL polytetrafluoroethylene liner loaded with titanium dioxide nanotubes, and the Fe / BiOBr precursor solution and titanium dioxide nanotube mixture were heated to 100°C and maintained for 11 h. After sufficient cooling, the reaction product was alternately rinsed several times with anhydrous ethanol and ultrapure water, and then placed in a vacuum drying oven and vacuum dried at 60°C for 6 h to obtain a nanoarray composite electrode.
[0060] The nanoarray composite electrode prepared in this example has similar performance to that of Example 1.
[0061] Comparative Example 1
[0062] In this comparative example, the nano-array composite electrode is prepared by the same method as in Example 1, except that Fe is not doped in the loading material in this comparative example. The nano-array composite electrode prepared in this comparative example is denoted as B-TNTAs.
[0063] The B-TNTAs prepared in this comparative example were subjected to transmission electron microscopy scanning, energy dispersive X-ray spectroscopy experiment, X-ray diffraction, cyclic voltammetry scanning, UV-light diffuse reflection, and degradation effect experiments, and the results were as follows: Figure 1-5 shown.
[0064] Comparative Example 2
[0065] The nanoarray electrode was prepared in the same method as in Example 1, except that the titanium dioxide nanoarray electrode was not loaded with Fe / BiOBr. The nanoarray electrode prepared in this comparative example was denoted as TNTAs.
[0066] The TNTAs prepared in this comparative example were subjected to transmission electron microscopy scanning, energy dispersive X-ray spectroscopy experiment, X-ray diffraction, cyclic voltammetry scanning, UV-light diffuse reflection, and degradation effect experiments, and the results were as follows: Figure 1-5 shown.
[0067] pass Figure 1 (a) It can be seen that, through the preparation method of the present invention, a nano-array electrode composed of a highly dense and ordered nanotube array can be successfully prepared, with an average tube diameter of 100 nm.
[0068] pass Figure 1 (b) It can be seen that the gaps between the mouths of TiO2 nanotubes can provide a certain space for the growth of BiOBr sheets, and after the growth of BiOBr sheets, the tubular structure of TiO2 nanotubes is not destroyed. Figure 1(b) It can also be observed that there is an angle between the BiOBr sheet and the TiO2 nanotube (most of which is 90°), and the BiOBr sheet does not cover the opening of the TiO2 nanotube. The average thickness of the BiOBr sheet is 25-40nm.
[0069] pass Figure 1 (c) It can be seen that the introduction of iron doping does not affect the growth direction and structure of the load material. The Fe / BiOBr sheet still maintains an angle with the TiO2 nanotube, and most of the angles are 90°. The Fe / BiOBr sheet does not cover the mouth of the TiO2 nanotube, which can effectively avoid the problem of reduced light absorption capacity caused by excessive blocking of the mouth by the load material. This shows that the preparation method of the present invention has good stability and can successfully prepare a nano-array composite electrode with an angle between the Fe / BiOBr sheet and the TiO2 nanotube.
[0070] Since the radius of the iron ion Relative to the bismuth ion radius The introduction of iron makes the growth of BiOBr crystals limited by shrinkage, and the size is reduced (e.g. Figure 1 (d1)), the average thickness is reduced to 6-12nm.
[0071] pass Figure 1 (d1-d6) It can be seen that the Ti, O, Bi, Br and Fe elements are uniformly present in the nanoarray composite electrode prepared by the present invention, proving that the preparation method of the present invention can prepare a TiO2 nanoarray composite electrode loaded with Fe / BiOBr.
[0072] pass Figure 2 It can be seen that the TNTAs in Comparative Example 2 correspond one-to-one to the anatase crystal plane standard card (JCPDS 89-4921), showing an anatase-type material. The B-TNTAs in Comparative Example 1 are still anatase-type, but due to the relatively low percentage of BiBOr, the relevant characteristic diffraction peaks (JCPDS 0393) are not obvious, which makes it impossible to clearly show them in the figure. The diffraction peaks of F / B-TNTAs in Example 1 are significantly increased, indicating that the introduction of Fe further increases the crystal strength of TNTAs, and the catalytic performance of the composite electrode is improved.
[0073] pass Figure 3It can be seen that the TNTAs in Comparative Example 2 did not show an oxidation peak, indicating that its electrochemical activity was poor. The B-TNTAs in Comparative Example 1 showed a clear oxidation peak at around 0.17 v, indicating that it had a certain electrochemical activity. The oxidation peak value of F / B-TNTAs in Example 1 was further improved relative to that of Comparative Example 1, and a reduction peak appeared at -1.26 v, indicating that Example 1 had better electrochemical performance than Comparative Example 1 and also had redox capabilities.
[0074] pass Figure 4 It can be seen that due to the light scattering caused by cracks on the surface, the TNTAs in Comparative Example 2 have a weak absorption band at 400-800nm, and the band gap absorption edge of the B-TNTAs in Comparative Example 1 has a slight red shift, and the light absorption ability is weak, while the F / B-TNTAs in Example 1 show strong light absorption ability in the entire visible light band, among which BiOBr and Fe 3+ The electron transition between the conduction band (CB) is one of the influencing factors.
[0075] pass Figure 5 It can be seen that the F / B-TNTAs of Example 1 showed stronger catalytic activity in photoelectrocatalysis. In the process of EE2 and CAP treatment, EE2 and CAP achieved 99.2% and 97.6% efficient degradation respectively. The performance of single photocatalysis or electrocatalysis in degrading EE2 was inferior to that of photoelectrocatalysis, and the degradation of CAP mainly depended on the electrochemical reduction of the photocathode.
[0076] In summary, the present invention prepares a TiO2 nanoarray composite electrode with an angle formed between Fe / BiOBr sheets and TiO2 nanotubes, which effectively enhances the light absorption capacity of TiO2 nanotubes and improves the catalytic activity of the composite electrode, ultimately enabling the composite electrode to have a high efficiency in treating new pollutants and to achieve efficient degradation of both EE2 and CAP.
[0077] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A method for preparing a TiO2 nano-array composite electrode, characterized in that: The preparation method comprises the following steps: (1) ultrasonically cleaning the titanium foil and then polishing it; (2) using the titanium foil treated in step (1) as an anode and the titanium plate as a cathode to perform electrolytic oxidation, washing the oxidized titanium foil, and then performing annealing treatment to obtain anatase TiO2 nanotubes; (3) dissolving bismuth nitrate pentahydrate and potassium bromide in ethylene glycol and stirring, and then adding ferric nitrate nonahydrate to obtain a Fe / BiOBr precursor solution; (4) hydrothermally reacting the Fe / BiOBr precursor solution obtained in step (3) with the anatase TiO2 nanotubes obtained in step (2), and then washing and drying the reaction product to obtain a TiO2 nanoarray composite electrode.
2. The preparation method according to claim 1, characterized in that: In the step (1), acetone, anhydrous ethanol and ultrapure water are used to ultrasonically clean the titanium foil in sequence, with each washing lasting 15 to 30 minutes.
3. The preparation method according to claim 1, characterized in that: In the step (1), the polishing liquid used for polishing is prepared from hydrofluoric acid, nitric acid and water in a volume ratio of HF:HNO3:H2O=1:4:5, and the polishing time is 30 to 60 seconds.
4. The preparation method according to claim 1, characterized in that: In the step (2), the electrolyte used for electrolytic oxidation is prepared from water, ethylene glycol and ammonium fluoride. First, water and ethylene glycol are mixed in a volume ratio of H2O:C2H6O2=1:49 to obtain a solvent, and then ammonium fluoride is added to the solvent in a mass ratio of NH4F:solvent=1:399 to obtain an electrolyte.
5. The preparation method according to claim 1, characterized in that: In the step (2), the electrolytic oxidation voltage is 30 V and the electrolytic oxidation time is 1 to 3 hours.
6. The preparation method according to claim 1, characterized in that: In the step (2), the annealing temperature is 450-550° C., the heating rate is 3-7° C. / min, and the holding time is 1-3 h.
7. The preparation method according to claim 1, characterized in that: In the step (3), the amounts of bismuth nitrate pentahydrate and potassium bromide are equal, the solid-liquid ratios of bismuth nitrate pentahydrate and potassium bromide to ethylene glycol are both 1-3 mmol:500 ml, and the solid-liquid ratio of ferric nitrate nonahydrate to ethylene glycol is 5-7 mmol:5000 ml.
8. The preparation method according to claim 1, characterized in that: In the step (3), after adding ferric nitrate nonahydrate, stirring is continued for 1 to 3 hours to obtain a Fe / BiOBr precursor solution.
9. The preparation method according to claim 1, characterized in that: In the step (4), the hydrothermal reaction temperature is 100 to 200° C., and the reaction time is 9 to 11 hours.
10. Use of the TiO2 nanoarray composite electrode prepared by the preparation method according to any one of claims 1 to 9 in the degradation of 17α-ethynyl estradiol and chloramphenicol.
Citation Information
Patent Citations
Preparation method of bismuth oxide halide-titanium oxide nanotube array composite photo-catalytic membrane
CN103285891A
Preparation method of Fe-doped oxyhalogen bismuth nanometer material
CN105251517A
Oxygen hole-containing BiOBr / TiO2 nanotube array composite electrode and preparation method thereof, and application of BiOBr / TiO2 nanotube array composite electrode to photoelectrocatalytic nitrogen fixation
CN112391651A
Preparation method and application of BiOBr / MIL-88A (Fe) composite photocatalyst
CN116273195A
Molybdenum oxide / bismuth oxybromide composite photocatalyst and preparation method thereof
CN116493028A